(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This article examines such concepts as "speech skills" and "speech skills", examines the works of domestic and foreign scientists. Particular attention is paid to the identification of semantic differences between the concepts of "speech skills" and "speech concepts".